ANALISIS PENGENDALIAN INTERNAL PEMBERIAN KREDIT PADA PT. BPR SINDANG BINAHARTA LUBUKLINGGAU - Wiguna, Kusnadi Yudha; Marliza, Yayuk; Kurniadi, Anton (Jurnal Media Ekonomi (JURMEK), 2020)
The purpose of this study was to determine the internal control of credit granting at PT. BPR Sindang Binaharta Lubuklinggau. This research is a qualitative descriptive study. Source of data used sourced from the primary form of observation of the operational activities of PT. BPR Sindang Binaharta Lubuklinggau and interviews with employees (commissioners, directors, internal audit team, and employees), as well as related customers regarding the internal control of lending at PT. BPR Sindang Binaharta Lubuklinggau. Secondary data obtained directly from PT. BPR Sindang Binaharta Lubuklinggau in the form of documentation relating to internal control of credit extension. The results showed the internal control of credit granting at PT. BPR Sindang Binaharta Lubuklinggau as a whole has been largely carried out well, but there are still weaknesses, namely the lack of objective AO marketing as a surveyor in credit lending decisions, and the absence of separation of authority, main tasks and functions between the AO marketing, analysts credit, and billing.